Molecular hematology - Provan, Drew, 1955-; Lazarus, Hillard M.; Ohio Library and Information Network (Hoboken, NJ : Wiley-Blackwell, 2024)
"The new and fully-revised volume of hematologic molecular biology for practicing and trainee hematologists Molecular Hematology is a comprehensive resource for hematologists to increase their understanding of the molecular basis of various blood diseases, their pathogeneses, and current and emerging molecular research and therapies. The impact of molecular research on the field of hematology is significant--molecular techniques are continuing to play a central role in in the diagnosis and treatment of blood diseases. Molecular characterization of genes and proteins has increased our comprehension of the causes of hematological diseases and led to the development of new drug therapies and recombinant proteins"--
Includes bibliographical references and index
Keywords: Blood -- Diseases; Hematologic Diseases; Molecular Biology -- methods